How do workers adjust when firms adopt new technologies? - Sabrina Genz; Terry Gregory; Markus Janser; Florian Lehmer; Britta Matthes (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We investigate how workers adjust to firms' investments into new digital technologies, including artificial intelligence, augmented reality, or 3D printing. For this, we collected novel data that links survey information on firms' technology adoption to administrative social security data. We then compare individual outcomes between workers employed at technology adopters relative to non-adopters. Depending on the type of technology, we find evidence for improved employment stability, higher wage growth, and increased cumulative earnings in response to digital technology adoption. These beneficial adjustments seem to be driven by technologies used by service providers rather than manufacturers. However, the adjustments do not occur equally across worker groups: IT-related expert jobs with non-routine analytic tasks benefit most from technological upgrading, coinciding with highly complex job requirements, but not necessarily with more academic skills.
Keywords: J23; J31; J62; O33; 330; technological change; artificial intelligence; employment stability; wages